VISUAL FIELD ASSESSMENT IN HYPERTENSION GLAUCOMA - Lešták, J; Fůs, M (Ceska a slovenska oftalmologie, 2021)
AIMS: The aim of the work is to verify the necessity of full-field perimetry test in incipient glaucoma. MATERIAL AND METHODS: The study included group of 16 incipient hypertension glaucoma (HTG group) patients without obvious changes in visual field and control group of 10 patients with normal ocular findings and value 1.0 of visual acuity. In both groups, full-field perimetry test was performed followed by a glaucoma perimetry test (rapid threshold strategy in both cases). Evaluated parameters were pattern defect (PD) and overall defect (OD) using Pearsons correlation coefficient. RESULTS: Strong correlation coefficient between PD (r = 0.74) and OD (r = 0.63) of both perimetry test were found in HTG group. Moderate correlation of PD (r = 0.54) and strong correlation of OD (r = 0.64) in control group. CONCLUSION: Results of the study shows, that expected changes of peripheral visual field will be recorded first in HTG group, but opposite is true. Perimetry glaucoma test is for incipient glaucoma sufficient to document the course and the examination of glaucoma disease.
Keywords: testy zrakového pole; Humans; overall defekt; Visual Field Tests; Hypertension; zraková pole; Intraocular Pressure; perimetry test; pattern defect; oční hypertenze; Glaucoma; brimonidin; hypertension glaucoma; Ocular Hypertension; hypertenze; Visual Fields; glaukom; lidé; nitrooční tlak